The Paris agreement on climate change a commentary (Commentaries., 2021)
viding in-depth coverage of each article of the Paris Agreement, this Commentary offers a comprehensive, legal analysis of this most recent and important international instrument on climate change. This provision-by-provision textual analysis examines the commitments that parties to the Agreement have made to undertake ambitious efforts to combat climate change and adapt to its effects, whilst providing additional support to developing countries. Describing the history, implementation and operation of the Paris Agreement, this Commentary is indispensable for obtaining a deep and nuanced understanding of the way in which the global community seeks to intensify its efforts to address climate change. Written by internationally renowned contributors, it discusses recent examples of implementation of the Agreement and nationally determined contributions (NDCs). Clearly written and accessible, this Commentary will be a vital resource for policy makers and government officials involved in climate change across the globe, whilst also being valuable for practitioners, scholars and students of climate change law and policy"--